2019
DOI: 10.1021/jacs.8b12870
|View full text |Cite
|
Sign up to set email alerts
|

Modular Total Synthesis and Cell-Based Anticancer Activity Evaluation of Ouabagenin and Other Cardiotonic Steroids with Varying Degrees of Oxygenation

Abstract: A Cu(II)-catalyzed diastereoselective Michael/aldol cascade approach is used to accomplish concise total syntheses of cardiotonic steroids with varying degrees of oxygenation including cardenolides ouabagenin, sarmentologenin, 19-hydroxysarmentogenin, and 5-epi-panogenin. These syntheses enabled the subsequent SAR studies on 37 synthetic and natural steroids to elucidate the effect of oxygenation, stereochemistry, C3-glycosylation and C17-heterocyclic ring. Based on this parallel evaluation of synthetic and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 98 publications
1
41
0
Order By: Relevance
“…Despite these numerous studies, the synthesis of highly oxygenated cardenolides, such as ouabagenin, represents a significant challenge, and only recent advances in catalysis and synthetic methodology allowed to overcome some of these challenges. Such landmark efforts include the recently disclosed syntheses of ouabagenin and 19‐hydroxysarmentogenin by the Deslongchamps, Baran, and Inoue groups as well as the studies by the Nagorny group that will be the focus of this mini‐review…”
Section: Syntheses Enabled By the Lewis Acid Catalysismentioning
confidence: 99%
See 4 more Smart Citations
“…Despite these numerous studies, the synthesis of highly oxygenated cardenolides, such as ouabagenin, represents a significant challenge, and only recent advances in catalysis and synthetic methodology allowed to overcome some of these challenges. Such landmark efforts include the recently disclosed syntheses of ouabagenin and 19‐hydroxysarmentogenin by the Deslongchamps, Baran, and Inoue groups as well as the studies by the Nagorny group that will be the focus of this mini‐review…”
Section: Syntheses Enabled By the Lewis Acid Catalysismentioning
confidence: 99%
“…Based on these findings, in 2015 Nagorny group demonstrated that the formation of 130 is possible in a highly enantioselective and diastereoselective fashion from simple and readily available building blocks 127 and 1 28 (Scheme ). [49g] Thus, it was demonstrated that readily available chiral bis (oxazoline) copper(II) complex 129 could promote Michael reactions with high levels of stereocontrol and the stereochemistry required for their subsequent elaboration to natural cardiotonic steroids (Scheme A). These Michael adducts could be subjected to various acidic or basic conditions that promote the intramolecular aldolization and provide various steroid‐like cores 130A‐J .…”
Section: Syntheses Enabled By the Lewis Acid Catalysismentioning
confidence: 99%
See 3 more Smart Citations